Adaptation of Gaming Features for Motivating Learners. (October 2017) - Monterrat, Baptiste; Lavoué, Élise; George, Sébastien
Background. Manylearning environments are quickly deserted by learners, even if they are efficient.Gamification of learning environments is a recent approach used to enhance learners' motivation and participation. Aim. People have various expectations and react differently faced with specific game mechanics. An important goal lies inautomatically adapting game mechanics according toplayer types . In this article, we study the gaming features that can be adapted in learning environments and theplayer model that can be used for the adaptation process. We propose an approach that aims topredict to which game mechanics a user is responsive, and to adapt the gaming features of the system according to this information. Methodology. An implementation was released, and evaluated through anquasi-experimental study with 59 middle school students, each one using the learning environment during three 45-minutes sessions. Results. The results validate the implementation of the system and show that theusers' activity can help topredict their profile . The adaptation process did not improve learners' engagement as expected, but it shows a path for future research toward an adaptive approach for learning environment gamification.